Pop-Up Book Media Development for Teaching Arabic Reading Skills: Pengembangan Media Buku Pop-Up untuk Mengajar Keterampilan Membaca Bahasa Arab - Isnaini, Salsabil Wahibatul Hidayah; Ammar, Farikh Marzuki (Indonesian Journal of Islamic Studies, 2025)
Background: Reading skills (maharah qira’ah) are essential in Arabic learning but often considered difficult due to limited instructional media. Specific Background: Students at MA Islamiyah Tanggulangin showed low motivation and difficulty understanding Arabic texts. Gap: Few studies have focused on developing pop-up book media for teaching qira’ah at the Madrasah Aliyah level. Aim: This study aims to develop a valid, practical, and effective pop-up book for improving students’ Arabic reading skills. Method: Using the R&D approach with the 4D model, the media was validated by experts and tested with students. Results: Validation achieved an average score of 97.33% (very valid), and student responses indicated high practicality. Novelty: The study introduces an interactive 3D visual medium to enhance motivation and comprehension in Arabic learning. Implications: The pop-up book serves as an innovative tool for improving engagement and learning quality in Arabic education. Highlights: Pop-up book enhances qira’ah learning motivation 3D visuals improve Arabic text comprehension Valid and practical learning media innovation Keywords: Pop-Up Book, Arabic Language, Qira’ah, Motivation, R&D